The mineral resources of Newfoundland, report of James P. Howley . for the year 1892 [electronic resource]. - Howley, James P., 1847-1918.; Newfoundland. Geological Survey. (St. John's, Nfld. : Robinson & Co., 1917)
Running title: Geological Survey of Newfoundland : report for 1892. Electronic reproduction. Mode of access: Internet. 44